2007
DOI: 10.1016/j.bbmt.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRB1*09 Is Associated with Increased Incidence of Cytomegalovirus Infection and Disease after Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Cytomegalovirus (CMV) infection is a major complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT); however, we have little information on the clinical association of various human leukocyte antigen (HLA) alleles with CMV infection. We reviewed medical records of 60 patients who underwent allo-HSCT. The effect of the 7 most frequent HLA alleles on the incidence of CMV infection and disease was analyzed, including HLA-A*02, A*11, A*24, B*13, B*40(60), DRB1*15, and DRB1*09. All the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…2012 [ 42 ] China, Beijing ALL, CML, MDS, AA, NHL 60 (87%) 0.92 0.9 Allo-HCT Du et al . 2007 [ 128 ] Taiwan, Kaohsiung, Taipei AL, NHL 117 (91.8%) 0.95 0.93 Allo-HCT Liu et al . 2012 [ 43 ] Japan, Tokyo Childhood AL 184 (81%) 0.76 0.72 UCBT Tomonari et al .…”
Section: Discussionmentioning
confidence: 99%
“…2012 [ 42 ] China, Beijing ALL, CML, MDS, AA, NHL 60 (87%) 0.92 0.9 Allo-HCT Du et al . 2007 [ 128 ] Taiwan, Kaohsiung, Taipei AL, NHL 117 (91.8%) 0.95 0.93 Allo-HCT Liu et al . 2012 [ 43 ] Japan, Tokyo Childhood AL 184 (81%) 0.76 0.72 UCBT Tomonari et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although accumulated evidence from extensive recent research indicates a role for HLA allele matching and haplotype matching between recipients and donors in transplant outcomes [28][29][30][31], the association between a particular HLA allele or HLA haplotype and the occurrence of infection has been scarcely explored. Du et al [32] demonstrated using multivariable analysis that HLA-DRB1*09, grade II to IV acute GVHD, and CMV-seronegative donors were associated with an increased incidence of CMV infection and disease after allo-HSCT, although their sample size was relatively small. We could not replicate this association.…”
Section: Discussionmentioning
confidence: 99%
“…RA-associated HLA alleles ⇒ susceptibility to certain trivial infections ⇒ increased infection incidence and duration [ 155 , 156 , 157 , 158 , 159 , 160 , 161 ].…”
Section: Methodsmentioning
confidence: 99%